(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This study examines the mechanisms and strategic approaches aimed at enhancing efficiency in the small business service sector. The service sector plays a decisive role in determining the overall performance of small businesses and the level of regional economic development. Therefore, identifying effective institutional, organizational, and economic mechanisms to improve service efficiency represents a pressing scientific and practical issue. The research analyzes key performance indicators, including profitability and service growth rate, to assess the effectiveness of small service enterprises. A conceptual mechanism is developed based on the interrelation between resource potential, transformational processes, and performance outcomes. The proposed model emphasizes digital transformation, innovation-driven management, service diversification, cluster development, and human capital enhancement as core strategic directions. Special attention is given to the role of digital platforms, service clusters, and diversification strategies in expanding market coverage, reducing transaction costs, and strengthening competitiveness. The study also explores international best practices, particularly the experience of China in digital integration and service ecosystem development, and assesses their adaptability to regional contexts.